Correlation Between Serum Entecavir Concentration and Virological Response in Patients with Chronic Type B Hepatitis - Wu, Zhengjie (Med Sci Monit, 2019)
BACKGROUND: This study was conducted to investigate the relationship between trough concentrations of serum entecavir and the virological response of patients with chronic type B hepatitis (CHB). MATERIAL/METHODS: A total of 59 CHB patients who had been receiving antiviral therapy with entecavir for >3 months were included in this study. Serum entecavir concentrations, HBV DNA levels, and other biochemical indicators were determined after drug treatments. RESULTS: The serum entecavir concentrations in the good response and poor response groups were 0.58±0.38 and 0.43±0.15 ng/mL, respectively. The antiviral efficacy was 52.38%, 65.63%, and 100% in low, middle, and high entecavir groups, respectively. The baseline HBV DNA level among the patients with poor response was significantly higher than in the group with good response. Among the 14 patients with a high viral load, 5 patients showed a good response and had a higher entecavir concentration than the other 9 patients with poor response. Entecavir in patients with cirrhosis was higher than in those without cirrhosis (0.63±0.45 ng/mL vs. 0.46±0.16 ng/mL), and the virological response rate in patients with cirrhosis was higher than in those without cirrhosis (83.33 vs. 51.43%). Cirrhosis progression was reversed in 3 patients with high serum entecavir concentration. CONCLUSIONS: Serum entecavir concentrations vary among individuals, and higher serum entecavir concentration is correlated with more efficient viral clearance. Therefore, for patients with poor response, high doses may be beneficial for viral clearance.